ROLE OF VETERINARY MEDICINE IN THE PREDICTION AND PREVENTION OF THE NEXT GLOBAL PANDEMIC - Sharof M. Tugizov (TADQIQOTLAR.UZ, 2024)
Accumulating evidence indicates that the spillover of viral pathogens from natural reservoirs into the human population may initiate a new global pandemic (Kache et al., 2021; Meadows et al., 2023; Plowright et al., 2024; Sparrer et al., 2023; Vora et al., 2022; Vora et al., 2023; Vora et al., 2024; Vora et al., 2021). Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which caused the COVID-19 pandemic (Ralph et al., 2020), is an excellent example of the spillover of zoonotic betacoronavirus from wild animals into humans (Sparrer et al., 2023; Tugizov, 2021; Tugizov S, 2003a, b, c, 2020).